(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper examines the use of Kahoot in English as a Foreign Language (EFL) classrooms, highlighting its potential to boost student motivation, participation, and language retention through gamified learning. While Kahoot offers real-time feedback and fosters inclusive engagement, it also presents challenges such as time pressure, superficial learning, and technological barriers. The study emphasizes the importance of balanced and purposeful implementation to maximize its educational impact.